Consumer Behavior Model: Brand Equity Mediated by Halal Awareness and Religiosity of Herbal Products Islamic Law Perspective - Rafiqi, Rafiqi; Widiastuti, Fitri; Lubis, Paulina; Darwisyah, Darwisyah (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2024)
Islamic economic theory emerged due to the theory of demand for goods and services. The demand for goods and services arises as a result of the wants and needs of real consumers and potential consumers. Herbal products, when associated with the Covid 19 issue, are currently a global conversation, so sales of these herbal products have experienced a significant increase compared to previous years. the Covid 19 pandemic disaster occurred. Due to the development of this herbal product sales trend, the brand equity of good quality products can affect consumer buying interest. Halal Awareness in halal-certified herbal products is a major construct that can help improve product brand reputation in intensively promoting consumer purchase intention models for halal brands. Consumer trust and behavior to buy herbal products is the key to the company's success in getting loyal consumers. An interesting question in this study is that the variables of brand equity and consumer behavior can mediate the relationship between halal awareness and religiosity variables. The purpose of this study is to analyze the relationship between consumer behavior, brand equity and halal awareness and religiosity. The research design is descriptive quantitative with a sample survey method. The research respondents were the people of Jambi City with a total sample of 200 people, but the number of samples collected was 210 people. The analysis tool uses PLS. From the results of this study, it is known that there is a positive relationship between consumer behavior, brand equity and halal awareness as a mediating variable. The study also shows that there is a positive relationship between consumer behavior and brand equity and there is a direct and significant positive relationship with brand equity. It is hoped that the results of this study will contribute empirically to thoughts related to consumer behavior, halal awareness, religiosity to brand equity.